PENGELOLAAN LINEN RUMAH SAKIT DAERAH dr. ADNAAN WD PAYAKUMBUH SUMATERA BARAT - Darwel Darwel Darwel; Rahmi Hidayanti (HUMAN CARE JOURNAL, 2019)
AbstractThe organization of environmental health of the hospital is carried out according to the environmental health requirements of the hospital. One of the supporting factors for hospitals in restoring patient health is the provision of linen. Regional General Hospital Dr. Adnaan WD Payakumbuh is a type C regional hospital. Linen infectious and non-infectious patients used ex-patients or former health service activities are produced every day and no sorting of infectious and non-infectious linen is not done. Washing linen uses 1 washing machine to wash all types of linen, does not have a linen carriage storage room, coordination of linen staff with other parts, especially in repairing facilities and equipment is not optimal, linen managers still do not use personal protective equipment (PPE). This study aims to determine the description of linen management at Adnaan WD Payakumbuh Hospital. The research is descriptive with an observation approach. The research instrument used a checklist and measurements referring to the Kepmenkes RI No 1204 in 2004. The data were analyzed descriptively in the form of tables and percentages. The results of the 80% linen washout, 100% linen collection stage, 100% transportation stage, 100% acceptance stage, 100% washing stage, 80% storage stage, and 100% distribution stage fulfilled the requirements.Keywords: infection, non-infection, linen, hospital